The little data book on gender 2009 (The World Bank, 2009)
The little data book on gender 2009 is a pocket edition of World Development Indicators (WDI) 2009 with a focus on gender-related statistics. It is intended as a quick reference for users of the WDI 2009 book and CD-ROM and WDI Online, and electronic subscription database. Together, they cover more than 800 indicators and span more than 40 years. The 209 country tables in the little data book on gender present the latest available data for the World Bank member countries and other economies with populations of more than 30,000. The 14 summary tables cover regional and income group aggregates.